Answer:
Explanation:
Expand it:
![3x^2 + 18x = -10](https://img.qammunity.org/2022/formulas/mathematics/college/bq1e7kik2dczag0u4c5en5r5djvb5a46t4.png)
Add 10 to both sides:
![3x^2 + 18x + 10 = 0](https://img.qammunity.org/2022/formulas/mathematics/college/xlixgcigrt51qsa6fiwz0nulydz0jxej2x.png)
Divide both sides by 3:
![x^2 + 6x + (10)/(3) = 0](https://img.qammunity.org/2022/formulas/mathematics/college/z7zkzdehx5xrccmgcadn8dsue09aayb0be.png)
Find a, b for
![(x + a)^2 + b = x^2 + 2x + a^2 + b \overset{!}{=} x^2 + 6x + (10)/(3)](https://img.qammunity.org/2022/formulas/mathematics/college/4ztko3d4pxk7iukvq2lebcr3eachrjgok8.png)
It’s
![a = (6)/(2) = 3 \land b = (10)/(3) - a^2 = 3 + (1)/(3) - 9 = -6 + (1)/(3)](https://img.qammunity.org/2022/formulas/mathematics/college/d6l71p7sv6tejjplawz2cxld2hfsw3vobw.png)
So, inserting it leads to:
![(x+3)^2 -6 + (1)/(3) = 0](https://img.qammunity.org/2022/formulas/mathematics/college/k2c6s7sxdzo1gypqspbikajfc2gibocelh.png)
Subtract b from both sides:
![(x+3)^2 = 6-(1)/(3)](https://img.qammunity.org/2022/formulas/mathematics/college/q27akfyep3vjcl9npxd5k5kibyxbbu8uej.png)
Apply square root to both sides and consider the two solutions:
![x + 3 = \pm\sqrt{6-(1)/(3)}](https://img.qammunity.org/2022/formulas/mathematics/college/9l1odntanlxrathsa0kg7f3aih06d4h88x.png)
Subtract 3 from both sides and you get
![x = -3 \pm \sqrt{6 - (1)/(3)}](https://img.qammunity.org/2022/formulas/mathematics/college/m1gqjc99bahpf5xhlk06rcnzcznr21hgix.png)